THE GHOSTS OF PORTALES: BANDITRY AND JuDICIAL PRACTICES IN CHILE, 1830-1850 - Palma Alvarado, Daniel (Revista de Historia Social y de las Mentalidades, 2012)
Focusing on the life-trajectory of an individual bandit in Chile’s central zone, and on his experiences dealing with justice and punishment, the article traces the constitution of the so-called “Portalean Order” in the field of criminal justice. It is especially concerned with the exchanges between the State and the bandits in a context where the strains between the government’s disciplinary goals and the resistance of those who were subjected to greater vigilance and punishment became particularly visible.